BOREAL BENTHONIC BIOTA OF THE LATE PALEOZOIC WORLD OCEAN - Ganelin V.G. (My University, 1997)
Spatial correlations of principal Late Paleozoic biochores usually referred to as boreal and tropical communities are discussed. The distribution of corresponding geographic ranges is shown to be inconsistent with the latitudinal zonation of the Late Paleozoic, and therefore the specific nature of these communities cannot be explained by differences in their latitudinal position. The emergence and distribution of "boreal" faunas show close correlations with the destruction of carbonate shelves and the ensuing formation of deep troughs on their sites. It supports the argument that "tropical" Late Paleozoic faunas may be attributed to communities of carbonate platforms whose ecological and paleogeographical type was inherited from the Early Paleozoic. Late Paleozoic "boreal" faunas represent a new ecologic and paleogeographic type of communities that inhabited marginal and median shelves of an extended system of deep basins. Analogues of these basins are intimated for Central Asia, Australia, and New Zealand. The character of sedimentation in these basins and peculiarities of their biota suggest a euxinic habitat for these faunas and the chemotrophic nature of the ecosystems similar to the environment of the chemotrophic communities revealed recently in rift valleys of modern oceans. The formation of Late Paleozoic basins of this type seems to comply with the protooceanic stage in the evolution of the lithosphere.
Keywords: Paleozoic; Paleozoic; Палеозой